Synthesis and photophysical studies of new pyrenylamino acids - Pereira, Goreti (2013)
Two new pyrenylamino acid derivatives were synthesized from beta-bromodehydroalanine derivatives in good yields using addition and elimination reactions. The photophysical properties of the two new pyrenylamino acids were studied in several solvents. Steady-state and time-resolved fluorescence measurements revealed that the bipyrenylamino acid undergoes excimer formation, this process being solvent dependent. Rate constants for excimer formation and dissociation were calculated. The monopyrenylamino acid exhibits a photophysical behavior similar to that of pyrene, including the sensitivity to solvent polarity. The results point to a potential use of these new pyrenyl derivatives as fluorescent probes for peptides and proteins.